Profile of the African Bread Fruit (Treculia africana) - Osabor, V.N.; Ogar, D.A.; Okafor, P.C.; Egbung, G.E. (Pakistan Journal of Nutrition, 2009)
The African bread fruit is produced by Treculia, a wild tropical evergreen tree and has immense potential as a nutritional source for man. We evaluated its chemical and nutritional properties as a first step in realizing its food value. The seed [Dry Mass (DM) basis] contained 8% moisture, 12.5% crude protein, 4.2% fat 2.3% ash 1.6% fibre and 73% carbohydrate. The carbohydrate and protein contents in it were much higher than other parameters studied. Compositions of toxicants in seeds were quite low with levels (mg/100 g) of 0.06±0.12 for hydrocyanide 3.0±0.11 for oxalate and 0.76±0.01 for phytate. For mineral elements, the contents (mg/100 gDM) were 587±0.2 for potassium (K), 186±0.2 for Magnesium (Mg) and 850±0.02 for zinc (Zn). The sodium (Na), Calcium (Ca), iron (Fe) and Copper (Cu) contents were negligible. Results of phytochemical screening of the extract showed, that it contained appreciable amounts of flavonoid, polyphenols, anthraquinones, saponins and cardiac glycosides. These secondary metabolites are known to have microbial activity as well as other physiological activity.